EUK-134, a synthetic superoxide dismutase and catalase mimetic, prevents oxidative stress and attenuates kainate-induced neuropathology - Rong, Yongqi (The National Academy of Sciences, 1999)
The present study tested the effects of EUK-134, a synthetic superoxide dismutase/catalase mimetic, on several indices of oxidative stress and neuropathology produced in the rat limbic system as a result of seizure activity elicited by systemic kainic acid (KA) administration. Pretreatment of rats with EUK-134 did not modify the latency for or duration of KA-induced seizure activity. It did produce a highly significant reduction in increased protein nitration, activator protein-1- and NF-κB-binding activity, and spectrin proteolysis as well as in neuronal damage resulting from seizure activity in limbic structures. These results support the hypothesis that kainate-induced excitotoxicity is caused, at least in part, by the action of reactive oxygen species. Furthermore, they suggest that synthetic superoxide dismutase/catalase mimetics such as EUK-134 might be used to prevent excitotoxic neuronal injury.